2017
DOI: 10.1038/s41598-017-00037-7
|View full text |Cite|
|
Sign up to set email alerts
|

Lipidome determinants of maximal lifespan in mammals

Abstract: Maximal lifespan of mammalian species, even if closely related, may differ more than 10-fold, however the nature of the mechanisms that determine this variability is unresolved. Here, we assess the relationship between maximal lifespan duration and concentrations of more than 20,000 lipid compounds, measured in 669 tissue samples from 6 tissues of 35 species representing three mammalian clades: primates, rodents and bats. We identify lipids associated with species’ longevity across the three clades, uncoupled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
1
47
0
1
Order By: Relevance
“…Several early studies quantified a number of biochemical and enzymatic parameters, revealing that the longer-lived species tend to have greater maintenance capacity, suffer less damage, and are more efficient at repair than the shorter-lived species (Holliday, 1997, 2006). However, until recently there had been very few cross-species comparative studies analyzing the entire mammalian transcriptome or metabolome (Bozek et al, 2017; Brawand et al, 2011; Fushan et al, 2015; Ma et al, 2015a; Ma et al, 2015b; Merkin et al, 2012). Besides the difficulty in obtaining reliable biological samples and the costs of large-scale omics studies, there are also some unique challenges in cross-species analyses that require particular attention.…”
Section: Challenges In Cross-species Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Several early studies quantified a number of biochemical and enzymatic parameters, revealing that the longer-lived species tend to have greater maintenance capacity, suffer less damage, and are more efficient at repair than the shorter-lived species (Holliday, 1997, 2006). However, until recently there had been very few cross-species comparative studies analyzing the entire mammalian transcriptome or metabolome (Bozek et al, 2017; Brawand et al, 2011; Fushan et al, 2015; Ma et al, 2015a; Ma et al, 2015b; Merkin et al, 2012). Besides the difficulty in obtaining reliable biological samples and the costs of large-scale omics studies, there are also some unique challenges in cross-species analyses that require particular attention.…”
Section: Challenges In Cross-species Studiesmentioning
confidence: 99%
“…In a recently published lipidome study, the levels of 13,000 to 21,000 hydrophobic compounds were quantified across 6 organs (brain cortex, cerebellum, heart, kidney, liver, and muscle) in 35 mammalian species belonging to rodents, primates, and bats (Bozek et al, 2017). Using logistic regression with elastic net penalty and adjusting for the confounding effects between lifespan and body mass, the authors constructed predictive models of the species’ maximum lifespans based on the lipid concentrations, with average prediction accuracy above 0.9.…”
Section: Cross-species Metabolome Ionome and Lipidomementioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the homeoviscous longevity adaptation hypothesis predicts a negative association between the degree of membrane fatty acid unsaturation and the longevity of organisms, which has received support in a comparative study of birds showing that longer lifespans correspond to species with longer fatty acids and higher proportions of MUFAs (traits that tend to be positively correlated; Galván et al ., ). An association between fatty acid unsaturation and longevity has also recently been reported in mammals (Bozek et al ., ). Consequently, it has been suggested that cell membrane has been an optimized feature during evolution (Pamplona, ; Naudí et al ., ), but this has never been tested.…”
Section: Introductionmentioning
confidence: 97%